Net profit signaling as a consideration for purchasing shares before dividend distribution decisions - Suryaningsum, Sri; Pronosokodewo, Baniady Gennody; Ayusulistyaningrum, Dyah (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
The study results provide implications for investors that net profit alone does not guarantee that dividends will be distributed. This study analyzes the behavior of stock investors who only pay attention to net profit when buying shares, especially in PT Clipan Finance Indonesia Tbk (issuer code CFIN). The CFIN Stock phenomenon is significant to study because the 2024 Financial Report presents a 2x increase in net profit compared to the previous year. However, the results of the 2024 GMS did not distribute dividends, while the previous year distributed dividends. The investment phenomenon ahead of the GMS is an investment with a dividend profit motive. This investor behavior is evident in the increasing stock price ahead of the GMS. This is the basis for this research. This investor behavior is analyzed by moving stock prices ahead of the GMS. This study compares the stock price during the month before the GMS with the stock price two months before the GMS. These results also indicate that investors only pay attention to net profit. A sharp increase in net profit does not necessarily guarantee that dividends will be distributed.